Constructions of Disability at a University in Hong Kong: Perspectives of Disabled Students, Staff Members, and Instructors - Christie Gilson; Stacy Dymond (Disability Studies Quarterly, 2011)
A qualitative study of university students with disabilities, instructors, and staff in Hong Kong was conducted to learn how disability was thought about and acted upon. Interviews with five disabled students, nine instructors, and six staff at a large university in Hong Kong were conducted over the course of a semester. Content analysis of the transcribed interviews yielded findings related to shame and stigma of disability, instructors’ admiration of disabled students, and disabled students’ varying levels of comfort in identifying as disabled. The medical model of disability framed how disability was viewed by many participants. Disabled students’ willingness to disclose their disabilities to university instructors varied depending on the situations they encountered. Implications from this research point to the need for articulation of best practices in self-advocacy as the presence of disability becomes more apparent and welcomed in Hong Kong and greater China.
Keywords: disability; higher education; disability studies; Hong Kong